Rancang Bangun Sistem Informasi Bank Sampah Induk Berbasis Aparatur pada Dinas Lingkungan Hidup Kota Bogor - Evan, Irsan Jossy; Jaenudin, Jejen; Widhyaestoeti, Dahlia (Teknik Informatika Universitas Pamulang, 2021)
Banking activities carried out by the Bank Sampah Induk Berbasis (BASIBA) at the Bogor City Environmental Service are still done manually using a notebook paper and then input to Ms. Excel sheet, such as customer data management, waste purchase transactions, withdrawal transactions, stock management and waste sales. So that the activities carried out are often found writing errors, as far as data is lost or damaged and the work process is quite long. To resolve this problem, BASIBA need media as data storage and changes the transaction activities in a computerized and efficient time. One solution is to design and build an information system that suits the needs of BASIBA, using an Software Development Life Cyle (SDLC) system design with a waterfall method. The system to be built uses a structured method with the PHP and MySQL programming languages as the system database server. Testing of the system that has been built using blackbox testing equivalence partitions techniques and a UAT questionnaire based on a likert scale to system users to ensure the level of success of the system design.